Design an Improved Hybrid Routing Protocol Strategy to Minimize Delay & Overhead for MANET - Dr. Deepak Dembla, Advin Manhar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mobile adhoc networks (MANET) are a self-coordinated wireless network that is worked without perpetual foundation and base station endorsement. In MANETs (Mobile Ad Hoc Networks) every single node activity goes about as the information source and communicator router. It notices its useful neighbours by making themselves by passing the nodes that got terminated of that correspondence range. In this paper, we designed the IHRP routing protocol with the help of combining the AODV, AOMDV and OLSR routing protocol with the network situation based routing adaptation. In the previous analysis, we identify AODV is more compatible for dynamic environment (where node motion is higher).The AOMDV routing protocol is useful for network load balancing and congestion control. OLSR is compatible for stable network which use as maximum link stability base routing. While we are designing the IHRP routing protocol through of the above (AODV, AOMDV and OLSR) protocol .We handle the network behaviour with better performance in any situation. Initially the RREP are broadcasted to find out the route. The poll of routing, select based on the network situation. The proposed IHRP start with a RREQ packet is to search the distance from its origin to its objective node. The network motion is higher than AODV protocol handle the particular situation but in any situation, while the 70% network node are stable then the route selection and transferring of data with the help of an OLSR routing protocol. The propose IHRP routing protocol also handle the network load and control the network congestion through the AOMDV routing protocol. Our proposed protocol IHRP also works in a hybrid manner while the source and destination belong in longer range such as different cluster. At that time situation based routing was followed between the clusters. We saw in the result part the comparison of IHRP and ZRP routing protocol. Execution of the improved hybrid routing protocol (IHRP) is much better than hybrid routing protocol (ZRP). In case of Packet Delivery Ratio analysis for IHRP and ZRP, we clearly show that The Packet Delivery Ratio is 97.99% by IHRP and 79.49% by ZRP, so we can say that the performance of packet delivery ratio in Improved hybrid routing protocol (IHRP) is much better than ZRP, where Improved hybrid routing protocol (IHRP) and hybrid routing protocol (ZRP) both performed the conjunction of proactive and reactive routing protocol features therefore we can say that Packet Delivery Ratio is better in improved hybrid routing protocol (IHRP) as compare to hybrid routing protocol (ZRP). We clearly show that the Normal Routing Load analysis for IHRP and ZRP where Normal Routing Load is 0.11% by IHRP and 4.72 % by ZRP, so we can say that performance of Improved Hybrid Routing Protocol (IHRP) in case of a Normal Routing Load is much less than the Hybrid Routing Protocol (ZRP). In case of overall parameter matrix (Normal Routing Load, Throughput, Packet Delivery Ratio and Average End To End Delay) the performance of Improved Hybrid Routing Protocol (IHRP) is much better than existing Hybrid routing protocol (ZRP).